Strategi Kebijakan Luar Negeri Brazil Pasca Bolsonaro dalam Revitalisasi Amazon Fund pada Periode Tahun 2019–2024 - Diandra Nadhifa Az Zahra; Nazwa Aurellia; Naysa Sakila Yasmin (Jurnal Transformasi Global, 2026)
This study aims to analyze changes in Brazil's foreign policy strategy following the Jair Bolsonaro administration's efforts to revitalize the Amazon Fund in the 2019–2024 period. The research focuses on how domestic policies and international dynamics influenced Brazil's decision to revive this conservation funding mechanism. The research method employed both quantitative and qualitative descriptive approaches. Quantitative data were obtained through official statistical documentation regarding Amazon Fund funding and Brazilian deforestation trends, while qualitative data were obtained through a desk review of literature, environmental reports, and related international policies. The results show that Bolsonaro's policies, characterized by environmental budget cuts, deregulation, and support for agribusiness expansion, led to a surge in deforestation, reaching its highest point since 2006, and prompted Germany and Norway to freeze their contributions to the Amazon Fund. When President Lula da Silva returned to office in 2023, the policy direction shifted significantly, marked by the strengthening of environmental institutions, the opening of international cooperation, and the reactivation of the Amazon Fund. The revitalization of the fund contributed to a reduction in deforestation of around 30 percent by 2023. Analysis through Two-Level Games and John Lovell's foreign policy strategy shows that Lula implemented a concordance strategy that balanced domestic demands and international pressure to restore Brazil's reputation in global environmental governance.